Plate IX: Carbonates of Lime, Marble - Kurr, J. G. (Johann Gottlob) (The Mineral Kingdom, 1859)
Figures 1-9. Carbonate of Lime, Marble. 1. Red-mottled Marble 2. The same [Red-mottled Marble] 3. Gryphitic Limestone 4. Variegated Fragmentary Marble 5. Reddish-yellow and Violet Flaked Marble 6. Pale Yellow and Violet Flaked Marble 7. The same [Pale Yellow and Violet Flaked Marble] 8. The same [Pale Yellow and Violet Flaked Marble] This hand-colored plate is part of the first edition English translation of the German Das Mineralreich in Bildern. The publication consists of two sections; the first is an introduction including topics such as the formation of crystals and chemical reactions of crystals; the second is devoted to the description of various mineral groups including precious stones, hornblende and augitic minerals, felspathic minerals, micaceous minerals, zeolitic minerals, calcareous minerals, and various salts and compounds. The final pages of the book contain twenty-four lithograph plates depicting crystalline structures and mineral forms. The first two plates are labeled A and B and the remaining plates are numbered I through XXII. The plates are hand-colored, using metallic finishes to create a lustrous effect.
Keywords: Mineralogy; Precious stones; Metals; Semimetals; Precious metals; Chemical elements; Marble